Reproductive outcome after cesarean scar pregnancy: A systematic review and meta‐analysis. (19th June 2020) - Morlando, Maddalena; Buca, Danilo; Timor‐Tritsch, Ilan; Cali, Giuseppe; Palacios‐Jaraquemada, Jose; Monteagudo, Ana; Khalil, Asma; Cennamo, Carmen; La Manna, Viviana; Liberati, Marco; D'Amico, Alice; Nappi, Luigi; et al.
Abstract: Introduction: To evaluate subsequent reproductive among women with a prior cesarean scar pregnancy (CSP). Material and methods: MEDLINE, Embase and ClinicalTrials.gov databases were searched. Inclusion criteria were women with a prior CSP, defined as the gestational sac or trophoblast within the dehiscence/niche of the previous cesarean section scar or implanted on top of it. The primary outcome was the recurrence of CSP; secondary outcomes were the chance of achieving a pregnancy after CSP, miscarriage, preterm birth, uterine rupture and the occurrence of placenta accreta spectrum disorders. Subgroup analysis according to the management of CSP (surgical vs non‐surgical) was also performed. Random effect meta‐analyses of proportions were used to analyze the data. Results: Forty‐four studies (3598 women with CSP) were included. CSP recurred in 17.6% of women. Miscarriage, preterm birth and placenta accreta spectrum disorders complicated 19.1% (65/341), 10.3% (25/243) and 4.0% of pregnancies, and 67.0% were uncomplicated. When stratifying the analysis according to the type of management, CSP recurred in 21% of women undergoing surgical and in 15.2% of those undergoing non‐surgical management. Placenta accreta spectrum disorders complicated 4.0% and 12.0% of cases, respectively. Conclusions: Women with a prior CSP are at high risk of recurrence, miscarriage, preterm birth and placenta accreta spectrum. There is still insufficient evidence to elucidate whether the type of management adopted (surgical vs non‐surgical) can impact reproductive outcome after CSP. Further large, prospective studies sharing an objective protocol of prenatal management and long‐term follow up are needed to establish the optimal management of CSP and to elucidate whether it may affect its risk of recurrence and pregnancy outcome in subsequent gestations.